Atezolizumab-Induced Stevens-Johnson Syndrome in a Patient with Non-Small Cell Lung Carcinoma - Phatcharawat Chirasuthat; Pamela Chayavichitsilp (Karger Publishers, 2018)
Atezolizumab is a humanized anti-PD-L1 immune checkpoint antibody that is currently used in many kinds of advanced carcinoma including metastatic non-small cell lung cancer. The cutaneous side effect profile reported only 20% of the patients which had only mild maculopapular rash that required no treatment. There is no case report of anti-PD-L1 antibody-induced Stevens-Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) eruptions. To the best of our knowledge, there is no case report of atezolizumab-induced SJS or SJS/TEN induced by anti-PD-L1 immune checkpoint antibodies. We believe that our report will be useful to dermatologists who are consultants in the inpatient settings, as atezolizumab is an anti-neoplastic agent that has a potential to be used in multiple malignancies.